2022
DOI: 10.1155/2022/7965433
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Autoimmune Cell in DA Neuron Apoptosis of Parkinson’s Disease: Recent Advancement

Abstract: Parkinson’s disease (PD) is a prevalent neurodegenerative disorder that manifests as motor and nonmotor symptoms due to the selective loss of midbrain DArgic (DA) neurons. More and more studies have shown that pathological reactions initiated by autoimmune cells play an essential role in the progression of PD. Autoimmune cells exist in the brain parenchyma, cerebrospinal fluid, and meninges; they are considered inducers of neuroinflammation and regulate the immune in the human brain in PD. For example, T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 201 publications
(214 reference statements)
0
10
0
Order By: Relevance
“…As with the gut microbiome, the pineal melatonin optimization of mitochondrial function (partly via the induction of the mitochondrial melatonergic pathway) better enables all cells to resist challenges posed by various stressors, including neighboring cells in a given intercellular microenvironment. There is a growing appreciation that a wide array of diverse medical conditions have 'autoimmune' aspects, such as Parkinson's disease [138] and schizophrenia [139]. The suppression of the mitochondrial melatonergic pathway also has consequences for the regulation of processes underpinning immune-mediated cell loss, classically referred to as 'autoimmunity', including via the regulation of intercellular processes.…”
Section: Pineal Melatonin and Systemic Mitochondriamentioning
confidence: 99%
“…As with the gut microbiome, the pineal melatonin optimization of mitochondrial function (partly via the induction of the mitochondrial melatonergic pathway) better enables all cells to resist challenges posed by various stressors, including neighboring cells in a given intercellular microenvironment. There is a growing appreciation that a wide array of diverse medical conditions have 'autoimmune' aspects, such as Parkinson's disease [138] and schizophrenia [139]. The suppression of the mitochondrial melatonergic pathway also has consequences for the regulation of processes underpinning immune-mediated cell loss, classically referred to as 'autoimmunity', including via the regulation of intercellular processes.…”
Section: Pineal Melatonin and Systemic Mitochondriamentioning
confidence: 99%
“…Myelo-peroxidase, an oxidant-producing enzyme that might harm dopamine neurons, is released by astrocytes, and it has been suggested that astrocytes could control microglial multiplication by releasing the cytokine granulocyte macrophage colony-stimulating factor (GM-CSF) [ 34 ]. By contrast, the marked and considerable increase in microglial activation was already consistently seen in PD animal models and Parkinson’s disease postmortem investigations or MPTP-induced parkinsonism [ 35 , 36 , 37 ]. This stimulation and expansion of microglia is known as the neuroinflammatory characteristic of Parkinson’s disease.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Neuronal damage may need prolonged exposure to proinflammatory cytokines such as IL-1, according to one theory [ 41 ]. On the cell bodies and processes of nigrostriatal neurons exist receptors for proinflammatory cytokines, including TNF-alpha, which probably renders the neurons that are vulnerable to the devastating impacts of cytokines produced by stimulated microglia [ 36 ]. This receptor modulation may begin or activate a caspase cascade, culminating in the neuron’s apoptotic death [ 35 , 36 ].…”
Section: Parkinson’s Disease and Microglia: A Look At Their Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrant deposits of α‐synuclein aggregates in the brain and the degeneration of dopamine (DA) neurons are clinical manifestations of Parkinson's disease (PD) in the substantia nigra pars compacta (SNpc). [ 1 ] The hallmark motor manifestations of PD include bradykinesia (slowness of movement), rigidity, resting tremors, and postural instability, all of which significantly impact the patient's ability to carry out daily activities. [ 2 ] The most prevalent pathogeny of PD with autosomal‐dominant hereditary is leucine‐rich repeat kinase 2 (LRRK2) missense mutations.…”
Section: Introductionmentioning
confidence: 99%